Peran Growth Mindset terhadap Career Adaptability Mahasiswa di Jawa Barat - Indah Puspitasari; Gianti Gunawan; Meta Dwijayanthy (Humanitas (Jurnal Psikologi), 2024)
Choosing a career is a crucial part of someone's life. A career is not just a means to fulfill one's needs; rather, it is a form of self-actualization and a way to build self-concept and social identity in society. This makes the phase of career exploration and job search challenging for individuals. Particularly for students who, after graduating from their education, will face a work environment different from the one they were in before. During the transition from the education world to the workforce, individuals are expected to have the ability to adapt effectively to meet the demands of entering the workforce. The ability to cope with the demands of new roles in the workplace is called career adaptability. Various studies have shown that career adaptability is influenced by several factors within the individual. The purpose of this study is to investigate the impact of growth mindset factors on students' career adaptability. The population of this study are students in West Java, with a sample size of 119 individuals. The data analysis technique involves using simple linear regression. The data analysis results indicate that mindset influences career adaptability.